Bahasa Indonesia - Narang, Umriani R. (Maliki Interdisciplinary Journal, 2024)
In an educational institution, as an educator, you will definitely carry out a learning process in the classroom that does not escape communication. When an educator knows good communication techniques, the interactions that occur between educators and students will run well or the learning process delivered by the educator will easy for students to understand. The word educator in Arabic is called mu'alim, mudarris, murabbi, muaddib, ustadz/usytadzah (coach, teacher, guide, lecturer). As a person whose profession is in the world of education, an educator must use good communication with students, school principals, parents, and fellow educators themselves. In communication, there are 2 techniques that you need to know, namely Verbal Communication and Non-Vebal Communication. Verbal communication is a communication technique conveyed by the sender of the message to the recipient orally and in writing (Marisa & Parianto, 2022). Meanwhile, non-verbal communication is a communication technique that conveys messages without words or in the form of symbols (Firdaus et al., 2020).